Ethnobotanical Insights into Plant Diversity Along the Ecotourism Corridor of Mount Prau in Purwosari Village, Indonesia - Abdullah, Muhammad; Hakim, Luchman; Siswanto, Dian; Liesnoor Setyowati, Dewi (Jurnal Pendidikan IPA Indonesia, 2024)
Examining ethnobotany in mountainous regions established as popular hiking destinations is essential for conservation initiatives. In this study, we aim to explore the ethnobotanical knowledge of the indigenous communities and to analyze the plant diversity in the ecotourism corridor to Mount Prau in Purwosari Village, Central Java, Indonesia. Ethnobotanical data was collected through semi-structured interviews with informants recruited via purposive sampling. An exploratory approach was used to inventory plant diversity along the ecotourism corridor of Mount Prau in Purwosari village. Our key informants comprised village officials, community leaders, Mount Prau caretakers, and basecamp managers. The findings indicated that the informants explained a total of 68 plant species, which were utilized by the community for various purposes. These plants served as valuable food sources, medicinal ingredients, and economic value, and they were also used for fodder, building materials, shade, and conservation purposes. In the ecotourism corridor in Purwosari village, which serves as the conservation trail for Mount Prau, a total of 117 plant species were identified through an inventory in this study. Finding some invasive alien plant species, such as Acacia decurens and Clidemia hirta, and an endangered species, Castanopsis argentea, highlights the importance of conservation efforts for protecting and preserving the diverse plant species found along the conservation trail to Mount Prau.